2011
DOI: 10.1007/s11104-011-0882-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen transfer from forage legumes to nine neighbouring plants in a multi-species grassland

Abstract: Legumes play a crucial role in nitrogen supply to grass-legume mixtures for ruminant fodder. To quantify N transfer from legumes to neighbouring plants in multi-species grasslands we established a grass-legume-herb mixture on a loamy-sandy site in Denmark. White clover (Trifolium repens L.), red clover (Trifolium pratense L.) and lucerne (Medicago sativa L.) were leaf-labelled with 15 N enriched urea during one growing season. N transfer to grasses (Lolium perenne L. and xfestulolium), white clover, red clover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
105
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(124 citation statements)
references
References 52 publications
(55 reference statements)
14
105
0
5
Order By: Relevance
“…The use of a grass in combination with a legume cover crop can improve N-release synchrony. Prior to termination, grass cover crops may take up N produced by legumes, while after termination, the higher C:N ratio of grasses moderates the leaching potential of the low C:N-ratio legumes [64,65]. Recent research in Maryland demonstrated that mixtures of hairy vetch and cereal rye, residues of which have a substantively higher C:N ratio than hairy vetch alone, can slow the decay rate of cover crop residues and reduce the quantity of early season plant-available N in the soil while still providing an important source of N for corn later in the season [52,58].…”
Section: Corn Fertility Managementmentioning
confidence: 99%
“…The use of a grass in combination with a legume cover crop can improve N-release synchrony. Prior to termination, grass cover crops may take up N produced by legumes, while after termination, the higher C:N ratio of grasses moderates the leaching potential of the low C:N-ratio legumes [64,65]. Recent research in Maryland demonstrated that mixtures of hairy vetch and cereal rye, residues of which have a substantively higher C:N ratio than hairy vetch alone, can slow the decay rate of cover crop residues and reduce the quantity of early season plant-available N in the soil while still providing an important source of N for corn later in the season [52,58].…”
Section: Corn Fertility Managementmentioning
confidence: 99%
“…The presence of legume improved the growth of S. splendida (Mucheru-Muna et al, 2010). Legume root systems did not give tough competition to the grass (Refliaty et al, 2009), as the grass acquire N from legumes through the decomposition and mineralization of N-rich legume plant litter and N transfer from the legume to grass (Pirhofer-Walzl et al, 2012). The total K value on SS/CP plot was >1 and on SS/CT was < 1 ( Table 3), indicating that S. splendida intercropped with C. pubescens contributed to the high productivity per unit of land compared to intercropping with C. ternatea (Yilmaz et al, 2008).…”
Section: Competition Indicesmentioning
confidence: 99%
“…The advantage of grass/ legume mix cropping in pasture is the possibility of N addition from the legume to the grass. Depending on the nitrogen content of the soil and the mix of legumes and grasses in a pasture, during the growing season legumes transfer approximately 40 kg N ha -1 to neighbouring plants (Pirhofer-Walzl et al, 2012). Grass/legume mixGrass/legume mixtures are more sustainable and better overcome unfavorable conditions as compared to their pure cultivation (Peyraud et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nodulated legumes are able to access atmospheric N 2 due to the symbiotic relationship that they establish with N-fixing bacteria (Russelle, 2008). Legumes have the potential to provide all the N required for their own growth, as well as transferring N to companion crops in intercropping systems (Hardarson & Atkins, 2003;Pirhofer-Walzl et al, 2012). N fixed by legume species can also be used by a succeeding crop in a crop rotation (Zotarelli et al, 2012;Monday et al, 2013).…”
Section: Study Site and Experimental Plot Characterizationmentioning
confidence: 99%